Calcium Pyrophosphate And Monosodium Urate Activate The NLRP3 Inflammasome Within Bladder Urothelium Via Reactive Oxygen Species And TXNIP - Harper, Shelby N (Res Rep Urol, 2019)
OBJECTIVE: To investigate the in vitro activation of the NLRP3 inflammasome within bladder urothelium by stone-forming components. Further, to describe the contributions of reactive oxygen species (ROS) and thioredoxin-interacting protein (TXNIP), an important structural component of the inflammasome, to this activation. METHODS: Urothelial cells were harvested and incubated overnight. For agonist studies, cells were treated with varying concentrations of calcium pyrophosphate (CPPD) and monosodium urate (MSU). For inhibitor studies, cells were treated with either N-acetylcysteine (NAC) (1 hr) or Verapamil (4 hrs) prior to incubation with either CPPD (62.5 ug/mL) or MSU (1.25 ug/mL) for 24 hrs. Untreated controls were incubated with ATP (1.25 mM) for 1 hr to maximally stimulate NLRP3 inflammasome activity (measured as caspase-1 cleavage of the fluorogenic substrate Ac-YVAD-AFC). Results are reported as a percentage of maximum ATP response. RESULTS: CPPD and MSU activate caspase-1 in urothelial cells in a dose-dependent manner, reaching ~50% and ~25% of the ATP response, respectively. Pre-treatment with the general ROS scavenger NAC reduces this activation in a dose-dependent manner. Additionally, activation was suppressed through treatment with Verapamil, a known downregulator of TXNIP expression. CONCLUSION: The stone components CPPD and MSU activate NLRP3 in an ROS and TXNIP-dependent manner in bladder urothelium. These findings demonstrate the importance of ROS and TXNIP, and suggest that targeting either may be a way to decrease stone-dependent NLRP3 inflammation within the bladder.